(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
Thermographic, crystallooptic and roentgeno-phase investigation of Rb3AlF6–K3YF6 system has been carried out. It has been shown thet the melting diagram of this system presents itself a continous row of solid solutions with minimum at 896°C and 75 mol % Rb3AlF6 content.